Impact of the fixed gantry angle approximation on dosimetric accuracy for helical tomotherapy plans. Issue 1 (18th December 2012) - Tudor, G. Samuel J.; Thomas, Simon J.
Abstract : Purpose: : The purpose of the work was to determine the accuracy of the dose calculation of off‐axis, small target helical tomotherapy treatments using 51 calculation angles, and to determine the increase in calculation angles required to improve the accuracy to acceptable standards. Methods: : A previously described dose calculation program [S. J. Thomas, K. R. Eyre, G. S. J. Tudor, and J. Fairfoul, "Dose calculation software for helical tomotherapy, utilizing patient CT data to calculate an independent three‐dimensional dose cube, " Med. Phys. 39, – (2012)10.1118/1.3668061 ] was modified to permit decomposition of each projection into several subprojections, allowing more accurate modeling of the temporal distribution of fluence within each beamlet. Four plans of small off‐axis spherical targets were recalculated several times with different numbers of subprojections, with the minimum dose to 95% of the PTV (D95% ) and the minimum dose to 2% of the PTV (D2% ) calculated for each, in order to determine the minimum number of subprojections required for accurate dose statistics. A further nine plans were used to determine the effect on conventional calculation accuracy of varying target size, target position, modulation factor, and pitch. For this analysis, the mean dose and equivalent uniform dose were considered in addition to D95% and D2% . Results: : The differences between calculations made using the 51 angle approximation and using the closest approximation to real treatment delivery were notable, with up to 11.0% overestimate of D95% for the cases studied. A previously unreported underestimate of dose to parts of the PTV was observed due to this effect, with D2% being underestimated by up to 3.3%. The effect is dependent on target size, position, modulation factor, and the angular distribution of fluence within the sinogram but not pitch. Decomposing each projection into three subprojections left differences in dose statistics that were of reduced magnitude but still appreciable. The effect of increasing the number of subprojections beyond five had little effect. Conclusions: : When applied to small, off‐axis targets, the limitations of the 51 calculation angle model can substantially affect the veracity of PTV dose statistics, including both underestimation and overestimation of dose depending on position within the PTV. Increasing the number of calculation angles by a factor of 5 reduces the effect to insignificant levels. While the latest release of TomoTherapy planning software will ameliorate the problem, the studied effect is best avoided by positioning small targets near to the bore center. Where this is not possible, it is recommended to ensure a high actual modulation factor and to use an unscaled delivery for patient‐specific quality assurance.